Myocardial Depression and Inhibition of Positive Inotropic Effect of Digoxin by Rosiglitazone - Said, Shehta A.; Nader, Manar A. (Fakultas Farmasi, Universitas Gadjah Mada, 2013)
This study was taken to investigate the effect of rosiglitazone (RGN) on the contractility of the isolated rat atrium as well as its possible inhibitory effect on positive inotropic effect of digoxin. RGN significantly increased the dose of digoxin required to produce cardiac arrest in anesthetized rats. RGN (10, 20, 40, 60, 80 & 100 µM) produced concentration dependant depressant effect on atrial contractility in both diabetic and non-diabetic animals with the depressant effect was more pronounced in diabetic rats than in non-diabetic ones. RGN also inhibited the positive inotropic effect of digoxin (0.1, 0.3 & 1µM) in isolated rat right atrium treated with 4 mg/kg orally daily for 21 days. Moreover, RGN also produced significant increase in serum K+ and decrease in Na+ levels in rats. These results indicate that RGN has a negative inotropic effect on the heart especially in diabetics and it inhibits the positive inotropic effect of digoxin.